Hukum sebagai Pilar Demokrasi dalam Perspektif Hak dan Kewajiban Warga Negara - Safitri, Giska; Vannesa, Bernadetha; Aziz, Fauzan; Safitri, Safitri; Aulia, Nabila Putri; Ramadhan, Adib Irfan; Hafizi, M Zainul (Journal of Civic Education, 2025)
This article aims to examine how law strengthens democracy through the principles of justice, political participation, and the protection of human rights. The study employs a systematic literature review combined with bibliometric analysis to map research trends, identify influential authors, and outline future directions in this field. Data sourced from the Scopus database were analyzed using VOSViewer to visualize citation networks, author collaborations, and keyword relationships. The findings indicate that democracy, human rights, and the rule of law constitute central and strongly interconnected themes, while governance and democratization serve as complementary dimensions. These results highlight a shift in research focus and the growing prominence of interdisciplinary approaches that integrate ethics, technology, and global governance. By synthesizing existing knowledge and mapping the intellectual landscape, this study offers a comprehensive understanding of the role of law in sustaining democracy and provides guidance for the development of future research.